Interpersonal Communication Management Between School Principals and Teachers in Fostering Discipline at MTs Darussa’adah Islamic Boarding School - Novita Sari; Syarifah Hidayani; Ahmad Zaki (Pusdikra-Publishing.com, 2024)
Social relationships are desired if someone feels that their self-esteem or sense of security will increase, and this relationship will be realized by carrying out harmonious communication. Interpersonal communication is a communication process that is considered the most effective and the process can be done in a very simple way. Apart from being an important element, interpersonal communication is a